(untitled) (INNOVATIVE ECONOMY, 2020)
Smulka O.I. PARTICIPATION OF ADVISORY SERVICES IN PROVIDING INNOVATIVE DEVELOPMENT OF AGRICULTURAL ENTERPRISES Purpose. The aim of the article is the consideration of problems and assessment of the prospects of using agricultural advisory services created in Ukraine to provide innovative development of agrarian enterprises. Methodology of research. The theoretical and methodological basis of the research was the position of modern science regarding the role of agricultural advisory services in the development of the agrarian sector of the Ukrainian economy. The followings methods were applied in this research: analysis and synthesis – to establish the patterns of development of agrarian advisory in Ukraine; comparative – to find out the peculiarities of the development of certain organizational and legal forms of agricultural advisory services; systematic approach – to reveal the mechanism of providing advisory services to the process of innovation development of agricultural enterprises; abstract and logical – for generalizations and formation of conclusions. Findings. The problems of using agricultural advisory services created in Ukraine to provide innovative development of agrarian enterprises are generalized. Approaches to the formation of a model of agricultural advisory activity in Ukraine are assessed critically. The expediency of involvement of the advisory services of experts from among the employees of agrarian universities, which promotes an efficient transfer of innovations, is substantiated. It is established that, in order to ensure the effective work of advisory services, their governing bodies should be formed from qualified managers capable of attracting funds for the financing of advisory activity, establishing contacts with agricultural producers. The principles of involvement in the organization of agricultural advisory services of the profile departments of regional and district state administrations are determined. Originality. The principles of forming a model of agricultural advisory activity in Ukraine, which supports the process of transfer of innovations in the activities of agrarian enterprises, were developed. Practical value. The results of the study can be used to substantiate the development of agricultural advisory services in Ukraine. Key words: agricultural advisory services; advisory services; agricultural enterprises; innovations; agrarian universities.